A retrospective analysis in the management of osteochondral lesions of the talus: Microfracture versus mosaicplasty (Annals of Medical Research, 2024)
Aim: This study compared the clinical and functional outcomes of arthroscopic microfracture treatment and open mosaicplasty for osteochondral lesions of the talus (OLT).Materials and Methods: The study was conducted between January 2005 and December 2012. Data for patients who underwent arthroscopic microfracture treatment or open mosaicplasty for OLT were retrospectively analyzed. The American Orthopedic Foot-Ankle Association (AOFAS) scoring system was used for functional assessment and the visual analog scale (VAS) score was used to evaluate pain level.Results:A total of 27 patients (13 microfracture, 14 mosaicplasty ) were included. In the microfracture group, median AOFAS score increased from 55.8 (29–80) before surgery to 82.6 (54–100) at the last follow-up, whereas VAS score decreased from 7.9 (6–10) to 2.3 (0–8). In the mosaicplasty group, median (IQR) AOFAS score increased from 63.3 (44–77) preoperatively to 90.5 (74–100) at the last follow-up, and VAS score decreased from 7.5 (6–10) to 1.5 (0–5).Conclusion: Arthroscopic microfracture treatment and open mosaicplasty are safe and effective treatment options for OLT. We could not see any clinical or functional difference between chondroplasty and microfracture when compared with mosaicoplasty. Microfracture can be chosen as the first treatment method in patients with cartilage lesions smaller than 2.5 cm2 because it is less invasive and can respond to rehabilitation more quickly.
Keywords: Arthroscopic microfracture; Mosaicplasty; Osteochondral lesion; Talus